Advocates’ Duties as Officium Nobile for Despicable Conduct: An Altruistic Outlook - Tampubolon, Manotar; Barimbing, Jhony; Natalia, Dea; Anzanis, Ghea Putri; Marakey, Melandito; Rossena, Gladys; Wijaya, Leonard Hendra; Niko Syahputra; Kristian, Petrus Roni; Michelle, Naomi (Technium Social Sciences Journal, 2021)
The role of an advocate is essential in providing legal aid to those in need, and their legitimate competence and professionalism are considered necessary. This is a descriptive method with statutory and conceptual underlying principles. Instead of constantly pursuing material for legal assistance, the advocate profession promotes ethical conduct in their duties as legal aid service providers. Every advocate is required to follow the Advocate’s ethical standards. The moral and ethical trend of advocates includes submission to Almighty God, the Rule on Advocates, and their own Clients. As a result, the profession of advocate is known as an officium nobile, or a virtuous profession. Advocates must follow the Indonesian Advocates Code of Ethics, which includes sanctions for unethical behavior. According to the authors, Indonesian lawyers do not appear to follow an ethical code in their work. Several lawyers are facing lawsuits for violating ethical principles in the defense of their clients because there is a widespread misconception that an advocate can be prosecuted for criminal or civil law violations. This unprovable assertion breaks the law and also the doctrine of equal treatment under the law.